Hispanic Parental Experiences of Learning a Child Identifies as a Sexual Minority. Issue 2 (15th March 2019) - Gattamorta, Karina A.; Salerno, John; Quidley-Rodriguez, Narciso
Abstract: Sexual minority youth (SMY) who do not feel loved and supported by their families face greater challenges and often experience various health disparities. The coming out process is often difficult for all SMY and their families. Although there is limited research on the impact of sexual orientation disclosure on families, there is even less that focuses exclusively on Hispanic families. This qualitative study explores the impact on a sample of Hispanic parents of having a child come out as lesbian, gay, or bisexual. The results demonstrate that although coming out is often challenging for SMY and their families, these challenges may be exacerbated for Hispanics due to cultural factors that contribute to children living at home longer and negative reactions to being gay. Parental reactions, impacts of disclosure on the family, and the impact of cultural factors are discussed. This study helps illuminate how cultural factors influence the coming out experience of Hispanic parents. These findings are important for understanding the experiences of these families to provide culturally appropriate resources for families navigating the coming out process.